Essential characteristic and necessity of normative and legal regulation of the defense resource management mechanism - Koretskyi, Andriy; Sotnyk, Viktoriia; Mogylevska, Viktoriia; Boiko, Ruslan; Kosaretskyi, Yevhenii (Social Development and Security, 2023)
Purpose: is to reveal the essence of the definitions “defense resources” and “defense resources management”; highlighting the main problems in the theoretical plane and directions for their solution.Method: the main research methods are methods of analysis and synthesis, induction and deduction, and structural analysis.The results of the study: In the conditions of limitation and lack of defense resources, a number of issues arise that relate to the system of their management, optimal distribution and effective use. In order for all the decisions made by the country's leadership to be effectively implemented, it is first necessary to allocate all types of resources that are necessary for this, to standardize the provisions in the governing documents that apply to them, and to highlight problems in the scientific and theoretical apparatus that subsequently affect the effectiveness of the system management of defense resources.Theoretical implications: further research will be aimed at implementing accepted changes in theoretical issues into the practical plane with the selection of relevant proposals for their solution.Papertype: descriptive, methodical.